Relationship between body composition and specific motor abilities according to position in elite female soccer players - Stankovic, M.; Capric, I.; Ðordevic, D.; Ðordevic, S.; Preljevic, A.; Konicanin, A.; Maljanovic, D.; Nailovic, H.; Mukovic, I.; Jelaska, I.; Sporiš, G. (International Journal of Environmental Research and Public Health, 2023)
Contemporary top-division soccer is characterized by high-intensity activity throughout the entire match, which also requires high levels of a wide range of the players` functional and motor abilities. Furthermore, motor and functional requirements vary in relation to the players` position on the pitch. In view of the above, the objective of this study was to determine any differences in body composition and specific motor abilities in relation to position. Twenty elite female soccer players (age: 20.90 ± 3.70 years; height: 166.95 ± 5.83 cm; weight: 58.97 ± 7.50 kg; training experience: 9.50 ± 4.11 years) were recruited for the purpose of this study. Based on their position within the team, the players were divided into three groups: defenders (N-7), midfielders (N-6), and forwards (N-7). The instruments used included the InBody770 (for body composition assessment), Optojump and Polar for the assessment of specific motor abilities. The results obtained indicate a strong link between the parameters body composition and specific motor abilities; however, the level of significance varies, as do the variables concerning specific motor abilities and body composition in relation to the players` position on the pitch. In accordance with these results, coaches and others working in the soccer industry should be apprised of the necessity of a tailored approach when it comes to planning the development of specific motor abilities, as well of with the importance of balanced body composition as prerequisites for achieving top results.